Análisis del comportamiento de las exportaciones de la región Loreto 2016-2020 - Santillan Pereyra, Weylerk (2022)
The thesis aims to analyze the evolution of exports from the Loreto Region period 2016 - 2020; determining the value of traditional and non-traditional exports in addition to identifying the product that was most affected by the state of emergency due to the COVID 19 pandemic, the research is descriptive and has a longitudinal non-experimental design, the sample is made up of all the records on traditional and non-traditional exports in the different economic activities that exist in SUNAT / ADUANAS; Exports in the period 2016-2020 reached the sum of 305.2 million US dollars at FOB value, of which 63 million correspond to non-traditional products and 242.2 million US dollars to traditional products. All products had a negative impact from the pandemic except for agricultural products, which in 2020 increased by 1.2 million US dollars at FOB value.